Decision Support For The Development Of Green Growth Tourism Strategies: Managing Complexity - McGrath, G. Michael; Law, Alexandra (Journal of Knowledge Management Practice, 2012)
The term ‘green growth’ refers to a system whereby material wealth is realized with due regard to environmental and social factors. Development of appropriate green growth policies is a complex task and, consequently, decision support technologies can be used to advantage here. The design and use of one such tourism destination decision support system is described in this paper. Key features of the system are that it facilitates the effective management of the inherent complexity of the analysis domain and allows iterative development with minimum impact on previous versions.